ANALISIS FAKTOR PENGENDALIAN KUALITAS TEH HITAM PADA PT. ABC DENGAN MENGGUNAKAN METODE PRINCIPAL COMPONENT ANALYSIS (PCA) - Anri Yosafat Sitompul; Dani Leonidas; Ekra Sanggala (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2023)
Indonesia is currently the seventh-largest producer in the world. One that produces tea in Indonesia is PT ABC. PT ABC is a State-Owned Enterprise engaged in the management, processing, and marketing of plantation products. The commodities produced by PT ABC are tea, rubber, palm oil, and cocoa. However, the author will focus on discussing black tea production at PT ABC The method used in this study is a qualitative method. The method used in this research is the Principal Component Analysis (PCA) method. Principal Component Analysis (PCA) is one-way identifying patterns in correlated data and expressing the information in a way that emphasizes discrepancies and distinctions. This method will analyze the priority factors for improvement that cause black products not to pass QC from several variables that have been setInterpretation of the results of factor analysis based on the value or magnitude of the loading factor previously described. Thus the 12 variables have been reduced to 2 factors that can affect black tea production does not pass QC at PT ABC, where factor 1 is a process factor then factor 2 is a raw material factor. factor analysis there are two factors that are priorities for improvement factor 1 with variables picking tea shoots exposed to sunlight (0.884) and room temperature regulation at the time of oxidation/fermentation is erratic (0.895). factor 2 with variable coarse tea shoots (0.957), Aroma of smoke in tea (0.952).